SISTEM PENGEMBANGAN KARIER PADA PERUM PERCETAKAN UANG RI - SARPANI NUGROHO (Jurnal Ilmiah Manajemen dan Bisnis, 2015)
As a security printing company, Perum Peruri members needs extra attention to the development ofhuman resources, including through career guidance system pattern. From the analysis of the externalenvironment, needs to be watched indicator changes due to government regulation, national economicgrowth, technological advances and the tendency of society. While the industry environment itself needsto understand the characteristics of the security printing business and the key success factors, given inIndonesia there are around 12 security printing company as a competitorMaximizing the effectiveness of the organizational structure with such a large number of orders, absolutely necessary governance can always trigger the achievement of a good working climate. The main focus onthe success of the company to achieve the strategic objectives is the human resources of all elements, bothmanagement and implementers, who are motivated by the availability of career pattern patterned well.The conditions of the research underlying the importance of the pattern of human resource development,especially on the pattern of coaching career, which started when an employee is placed up to the releaseMap of well-managed career in strategic aspects include structural lines and functional lines are supportedwith educational and training programs are expected to form the desired profile plenary employees, inorder to support the achievement of strategic objectives. Through a theoretical approach "BostonConsultant Group" in the 4-quadrant matrix relationship concludes there are problems that must becorrected include: a managerial role empowering role of individuals, research and development, security,and installation as well as the organizational culture.